The Epidemiology of Valvular Aortic Stenosis. Prevalence, incidence, mortality, risk factors and progression of aortic stenosis in a general population. The Tromsø Study. - Eveborn, Gry Debora Wisthus (UiT The Arctic University of Norway, 2015)
The papers of this thesis are not available in Munin. Paper I. The evolving epidemiology of valvular aortic stenosis. The Tromso Study. Eveborn GW, Schirmer H, Heggelund G, Lunde P, Rasmussen K. Available in Heart, 2013;99:6 396-400 Paper II. Assessment of risk factors for developing incident aortic stenosis: the Tromsø Study. Eveborn GW, Schirmer H, Lunde P, Heggelund G, Hansen JB, Rasmussen K. Available in European Journal of Epidemiology (2014) 29:567–575 Paper III. Risk of developing Aortic Stenosis in subjects with subclinical Mean Aortic Valve Gradients. The Tromsø Study. Eveborn GW, Schirmer H, Heggelund G, Rasmussen K. (Manuscript). With datasets from 3 repeated echocardiographic examinations (1994, 2001 and 2008) of a random sample of initially 3,273 participants in the Tromsø Study, we were able to give descriptive and analytical epidemiologic data on degenerative aortic valve disease. Aortic valve stenosis (AS) was defined as a mean aortic valve gradient ≥15 mmHg. There were 164 subjects with AS. We found that prevalence consistently increased with age, average values being 0.2% in the 50-59 year cohort, 1.3% in the 60-69 year cohort, 3.9% in the 70-79 year cohort and 9.8% in the 80-89 year cohort. The incidence rate of AS was 4.9‰/year. The mean annual increase in mean transvalvular pressure gradient was 3.2 mmHg. The increase was lower in mild AS than in more severe disease, disclosing a non-linear development of the gradient, but with large individual variations. Mortality was not significantly increased in the asymptomatic AS-group (HR=1.28), nor in those who received aortic valve replacement (n=34, HR= 0.93), compared with the general population. 132 participants were diagnosed with incident AS. Cox proportional hazards regression disclosed age (HR 1.11, 95%CI 1.08 to 1.14), systolic blood pressure (HR 1.01, 95%CI 1.00 to 1.02), active smoking (HR 1.71, 95%CI 1.09 to 2.67), and waist circumference (HR 1.02, 95%CI 1.00 to 1.03) as independent predictors of incident AS. Analysis of risk factors ...